2021
DOI: 10.4103/njm.njm_157_20
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Isolates of Surfaces in the Neonatal Intensive Care Unit of Enugu State university Teaching Hospital, Parklane, Enugu, and Their Antibiotic Susceptibility Patterns

Abstract: Introduction: The duration of admission in the hospital, mortality rates, and care costs is increased in Neonatal Intensive Care Unit (NICUs) by nosocomial infections (NIs). There is a need for routine and regular environmental sampling in NICUs. Methodology: This was a cross-sectional study conducted in the NICU of Enugu State University Teaching Hospital. The researchers collected samples for culture from equipment and hospital surfaces in the unit. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…These findings are in tandem with that documented in Asaba Nigeria in which majority of the cases were discharged [11]. This finding is in contrast to that found in Enugu Nigeria in which 43.5% of the CHER admissions were discharged home and Benin City where only 30.4% were discharged [2,9]. Few (15.64%) of the patients seen in the CHER were admitted into the paediatric wards.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…These findings are in tandem with that documented in Asaba Nigeria in which majority of the cases were discharged [11]. This finding is in contrast to that found in Enugu Nigeria in which 43.5% of the CHER admissions were discharged home and Benin City where only 30.4% were discharged [2,9]. Few (15.64%) of the patients seen in the CHER were admitted into the paediatric wards.…”
Section: Discussionsupporting
confidence: 72%
“…Also the high vulnerability of this class of people to different medical ailments and poor practice of childhood survival strategies that prevent common childhood morbidities and mortalities could be contributory to this finding. Other authors have also observed paediatric medical conditions as being the commonest conditions in the CHER in their studies [1,2,8,9,11].Malaria (26.3%) was the most common condition seen in CHER. This was followed closely by AGE which constituted 23.3%, pneumonia (13.4%) and sepsis (7.4%) respectively.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations